Clinical outcome of trans-portal anatomic anterior cruciate ligament reconstruction with quadrupled semitendinosus graft - Kumar Jha, Ranjib; Thapa, Santosh; Rajthala, Ashish (Birat Journal of Health Sciences, 2024)
Introduction: The anterior cruciate ligament (ACL) injury is one of the most common injuries of knee. Arthroscopic reconstruction of ACL is standard approach, but controversy still remains regarding choice of graft. Objective: The objective of study is to see clinical outcome of quadrupled semitendinosus graft for ACL reconstruction. Methodology: This was a prospective clinical study of patients undergone single bundle ACL reconstruction with quadrupled semitendinosus autograft between February 2021 to July 2022 in our orthopedic department. All eligible patients who met inclusion criteria were evaluated in terms of knee stability subjectively and objectively before operation and at one year after operation. Results: There was total 33 patients, out of which 27 were male and 6 were female. The mean age was 27.5±8.2 years and most common mode of injury was RTA in 14 patients (43%) followed by sporting activities in 13 patients (39%) and fall from height in 6 patients (18%). The average diameter of graft was 8.03±0.35mm. The mean Lysholm score was 92.3±5.1 (range 79–99). Seventy percent patients returned to preinjury activity level whereas 30% decreased their activity level. In our study 31 patients (94%) had negative pivot shift test which indicates very high rate of knee stability. Conclusion: The quadrupled semitendinosus graft shows excellent result for ACL reconstruction both subjectively and clinically in our study. This method helps to save Gracilis tendon and also increases graft diameter.